2014
DOI: 10.1155/2014/283718
|View full text |Cite
|
Sign up to set email alerts
|

Aero-Engine Fault Diagnosis Using Improved Local Discriminant Bases and Support Vector Machine

Abstract: This paper presents an effective approach for aero-engine fault diagnosis with focus on rub-impact, through combination of improved local discriminant bases (LDB) with support vector machine (SVM). The improved LDB algorithm, using both the normalized energy difference and the relative entropy as quantification measures, is applied to choose the optimal set of orthogonal subspaces for wavelet packet transform- (WPT-) based signal decomposition. Then two optimal sets of orthogonal subspaces have been obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Lagrange multiplier i a also incorporates constraint in the quadratic equation and converts it into an unconstrained one. In this research, the value of w is assigned the same as that taken by [20][21][22][23][24][25]. With this treatment, the objective function can be rewritten as given in equation (2).…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…Lagrange multiplier i a also incorporates constraint in the quadratic equation and converts it into an unconstrained one. In this research, the value of w is assigned the same as that taken by [20][21][22][23][24][25]. With this treatment, the objective function can be rewritten as given in equation (2).…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…Considering that a single dissimilarity measure for the optimal subspace selection may not be able to capture all the characteristic information of the signals, both the relative entropy, which describes the difference of energy distribution in different classes of signals, and the normalized energy difference between different classes of signals are used as the dissimilarity measures in this study, which have been identified as good measures for classification. The details of these two measures can be seen in [30]. Features from these subspaces can then be extracted to distinguish different classes in a given set of data that belong to several classes.…”
Section: Fault Diagnosis Based On Optimized Wavelet Packet Transformmentioning
confidence: 99%
“…SVMs are a family of learning machines that are based on methodological contributions from statistical learning, kernel-based processing, functional analysis, and optimization theory [26]. SVM approaches have been proposed for classification [19,[26][27][28], regression [26,29], and probability density modeling [30].…”
Section: Svm Classificationmentioning
confidence: 99%
“…Generalization to classes ( > 2) is usually achieved by decomposing the multiclass problem into a collection of binary subproblems [19,26,28]. Here, the one-againstone (OAO) approach is used, which is usually a good tradeoff between accuracy and computational burden.…”
Section: Svm Classificationmentioning
confidence: 99%